2019
DOI: 10.1002/icd.2138
|View full text |Cite
|
Sign up to set email alerts
|

How important is early home environment in the prediction of attention‐deficit hyperactivity disorder in adolescence? The protective role of early cognitive stimulation

Abstract: Attention‐deficit hyperactivity disorder (ADHD) is highly heritable; however, an adequate home environment may moderate its development. This study examined the early home environment of 70 male adolescents (M age = 13.5 years, SD = 0.95) participating in a prospective high‐risk longitudinal study. Results demonstrated that adolescents who were eventually diagnosed with ADHD tended to have higher home chaos and less enriched home environments in early childhood. Within the different aspects of enriched home en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Cognitive stimulation is another need of children [14,15]. Opportunities for early learning such as reading to the child during the first 1000 days has been associated with improved language development, mathematical and problem-solving capacity and higher earning capacity later in life [23][24][25]. In addition, studies have shown that parental warmth, nurturance and responsiveness during the first 1000 days of life, affect infants' emotional regulation, capacity for wealth creation, behavioural problems, health and cognitive development throughout their lifespan [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive stimulation is another need of children [14,15]. Opportunities for early learning such as reading to the child during the first 1000 days has been associated with improved language development, mathematical and problem-solving capacity and higher earning capacity later in life [23][24][25]. In addition, studies have shown that parental warmth, nurturance and responsiveness during the first 1000 days of life, affect infants' emotional regulation, capacity for wealth creation, behavioural problems, health and cognitive development throughout their lifespan [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that a cognitively stimulating home environment might improve children's self-regulation, which in turn might enhance their ability to be attentive, especially in school settings. The inverse association between learning stimulation and ADHP is still found after controlling for parental ADHD symptoms, other aspects of the home environment, as well as other environmental risk factors like socioeconomic status, birth weight, and alcohol/cigarette exposure (Einziger et al, 2019;Jester et al, 2005;Mulligan et al, 2013). Additionally, it appears that the in uence of an enriched home environment on later ADHP might be speci c to the cognitive rather than the emotional or physical aspects of the environment (Einziger et al, 2019;Schmiedeler et al, 2014).…”
Section: Learning Stimulationmentioning
confidence: 98%
“…This is in line with previous ndings that have supported the role of learning stimulation in the development of ADHD. For example, Einziger et al (2019) found that higher levels of cognitive stimulation at age 4 predicted lower risk for ADHD diagnoses in adolescence. The literature also supports the role of learning stimulation beyond the confounding in uence of factors like low SES (e.g., Bradley et al, 1989;Mulligan et al, 2013;Schmiedeler et al, 2014), which is consistent with our ndings.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations